(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
The world economy is undergoing a change. All business is becoming data as a result of internet technologies. The pace of technology development is so fast that emergent ecommerce is now influencing every facet of how business is but will be done, causing major change in economic environment. Corporations’ reach has been widened thanks to the Internet. Because of the large quantity of company information made accessible by the worldwide Web, which means bringing together the information transferred between firms, between a company and its consumers, or between various divisions of a business, new business prospects are increasing tremendously. Any firm will no longer be able to disregard data virtual value chains on such an operational and strategic level. This study examines the extent, unique aspects of e-commerce technologies, including potentials of e- commerce. It also creates a basis for recognizing electronic commerce’s prospects or major research concerns. The focus is on combining technology or business concepts in an interdisciplinary approach.